Does pre-employment card program improve Indonesian youth labor market performance in pandemic era? - Muhammad Salahudin Al Ayyubi; Devanto Shasta Pratomo; Ferry Prasetyia (Cogent Economics & Finance, 2023)
The pre-employment card program, a training voucher policy initiated by Indonesian government in the beginning of 2020 emerged as an alternative instrument in economic recovery, including for youth affected by the COVID-19 pandemic. Using the multinomial logit and Lee's selection-biased corrections, the objectives of the study then are to see the effect of the program on (1) employment status and (2) income of youth during the pandemic. The data used are sourced from the 2020 National Labor Force Survey. The results show that the participation of youth in the program increases participation in the labor market, especially in the informal sector. However, the results show that there is still no significant effect of the program on income in all employment status, suggesting a potential lagged income effect of the program.
Keywords: 330; employment status; Indonesia; pre-employment card; Sakernas; youth